2019
DOI: 10.3390/ijms20081867
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characteristics of Pancreatic Epsilon Cells

Abstract: Pancreatic endocrine cells expressing the ghrelin gene and producing the ghrelin hormone were first identified in 2002. These cells, named ε cells, were recognized as the fifth type of endocrine cells. Differentiation of ε cells is induced by various transcription factors, including Nk2 homeobox 2, paired box proteins Pax-4 and Pax6, and the aristaless-related homeobox. Ghrelin is generally considered to be a “hunger hormone” that stimulates the appetite and is produced mainly by the stomach. Although the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 85 publications
0
19
1
3
Order By: Relevance
“…It was intriguing to note that not all secretory granules of pancreatic beta cell contain both insulin-and ghrelin-positive nanoparticles. Although reports have shown that ghrelin is produced by epsilon cells of the pancreas [57,59], we did not find ghrelin-positive granules in other cell types. Other studies have reported that ghrelin co-localized sporadically with glucagon in early and late fetal periods and eventually separate later in adult life [60].…”
Section: Body Weight Gain Blood Glucose and Glucose Tolerancecontrasting
confidence: 99%
“…It was intriguing to note that not all secretory granules of pancreatic beta cell contain both insulin-and ghrelin-positive nanoparticles. Although reports have shown that ghrelin is produced by epsilon cells of the pancreas [57,59], we did not find ghrelin-positive granules in other cell types. Other studies have reported that ghrelin co-localized sporadically with glucagon in early and late fetal periods and eventually separate later in adult life [60].…”
Section: Body Weight Gain Blood Glucose and Glucose Tolerancecontrasting
confidence: 99%
“…ε cell was the fifth endocrine cells identified in pancreatic islet cells, which producing the ghrelin hormone (Wierup et al, 2002). Ghrelin functions through regulating the functions of other endocrine cells (Sakata et al, 2019). Ghrelin inhibits the secretion of insulin from β cells via paracrine interaction between δ cells and β cells.…”
Section: ε Cell and Ghrelinmentioning
confidence: 99%
“…Ghrelin is a 28-amino-acid peptide produced mainly by the neuroendocrine cells named P/D1 in humans in the oxyntic mucosa of the gastric fundus, and to a far lesser extent in the duodenum, and also in the epsilon pancreatic islet cells (69,70). Ghrelin is cleaved from the 117-amino-acid preproghrelin protein encoded by the human ghrelin gene on chromosome 3p25-26.…”
Section: The Ghrelin Leptin and Melanocortin System In An And Bnmentioning
confidence: 99%